Science and Engineering Implementation: A Case Study on Edible and Renewable Car Activity - Hilmi Doğan; Ayşe Savran Gencer; Kadir Bilen (Araştırma Temelli Etkinlik Dergisi, 2017)
The Edible and Renewable Car Contest activity that would allow students to experience objectives of secondary school science, mathematics, technology, and design courses was conducted in this study. An engineering design cycle was implemented. The research group consisted of five female and seven male students in the 7th grade. A case study was used as a qualitative research design. Semi-structured interviews and reflective open-ended questions were analyzed by descriptive analysis. The performances of the students were evaluated with Edible and Renewable Car Activity Rubric and Peer Assessment Rubric. Data analysis revealed that even though the students expressed the view that they had difficulty in team work and material supply, they expressed that the activity was fun, they had an idea about the similarities and differences between science and engineering practices, and also they enjoyed applying the design cycle.